Assessment of Bioprotect's Biodegradable Balloon System as a Rectal Spacer in Radiotherapy: An Animal Study on Tissue Response and Biocompatibility - Yuval Ramot; Tal Levin-Harrus; Adva Ezratty; Michal Steiner; Nati Ezov; Abraham J. Domb; Muhammad Abdel-Haq; Shaul Shohat; Liron Aperman; Lee Adler; Oleg Dolkart; Abraham Nyska (MDPI AG, 2023)
Prostate cancer is a significant health concern for men, emphasizing the need for effective treatment strategies. Dose-escalated external beam radiotherapy shows promise in improving outcomes but presents challenges due to radiation effects on nearby structures, such as the rectum. Innovative techniques, including rectal spacers, have emerged to mitigate these effects. This study comprehensively assessed tissue responses following the implantation of the Bioprotect biodegradable fillable balloon as a rectal spacer in a rat model. Evaluation occurred at multiple time points (4, 26, and 52 weeks) post-implantation. Results revealed localized tissue responses consistent with the expected reaction to biodegradable materials, characterized by mild to moderate fibrotic reactions and encapsulation, underscoring the safety and biocompatibility of the balloon. Importantly, no other adverse events occurred, and the animals remained healthy throughout the study. These findings support its potential clinical utility in radiotherapy treatments to enhance patient outcomes and minimize long-term implant-related complications, serving as a benchmark for future similar studies and offering valuable insights for researchers in the field. In conclusion, the findings from this study highlight the safety, biocompatibility, and potential clinical applicability of the Bioprotect biodegradable fillable balloon as a promising rectal spacer in mitigating radiation-induced complications during prostate cancer radiotherapy.